Preclinical Assessment in Juvenile Sheep of an Allogeneic Bone Tissue Engineering Product with Wharton’s Jelly Mesenchymal Stromal Cells - Raquel Cabrera-Pérez; Irene Carreras-Sánchez; Ángela Roig-Molina; Alba López-Fernández; Irene Portas-Torres; Laura Batlle-Morera; Roberto Vélez; Joaquim Vives (Cells)
Secondary osteonecrosis (ON) is a common complication in paediatric cancer survivors. Combining multipotent mesenchymal stromal cells (MSCs) with core decompression surgery halts disease progression and stimulates bone regeneration. However, the success of advanced therapy medicinal products (ATMPs) requires versatile “off-the-shelf” tissue engineering products (TEPs). This study evaluated the safety and efficacy of TEPs loaded with allogeneic MSCs from Wharton’s jelly (WJ-MSCs) in a large-animal model of bone regeneration to support a paediatric investigational plan for ON patients. WJ-MSC-laden fibrin-based hydrogels combined with a synthetic bone substitute (PRO-DENSETM) were tested in 16 juvenile sheep (8 males and 8 females) distributed in four experimental groups. Each animal received four cylindrical bone defects in the femoral and tibial epiphyses and was assessed at 6 and 12 weeks. Safety was confirmed, and bone regeneration was observed across all groups. A combination of WJ-MSCs with PRO-DENSETM led to improved histological scores, osteogenesis, and construct integration. Trabecular bone volume also increased more in cellular groups over time. However, effects were inconsistent across groups, reflecting the variability seen in clinical trials and highlighting the significant impact of factors such as immunogenetic compatibility, MSC batch potency, and interaction with the recipient’s microenvironment on the therapeutic effectiveness and successful clinical translation of allogeneic ATMPs.